CLINICAL MANIFESTATION, DIAGNOSIS, AND MANAGEMENT OF NOTOEDRES CATI IN A DOMESTIC CAT: A CASE REPORT FROM ARMONIA PET CARE, MAKASSAR, INDONESIA - Anjani Marisa Kartikasari; Ayu Bunga Qanita Putri Prabowo; Muhammad Raynaldi Tamsyir; Besse Anisa Mufida Sahrani; Lydia Cahyatrianti (Buletin Veteriner Udayana, 2025)
Notoedric mange, caused by the ectoparasite Notoedres cati, is a significant dermatological condition in domestic cats (Felis catus). This case report aims to describe the clinical presentation, diagnostic approach, and therapeutic management of N. cati infestation in a young cat, emphasizing its zoonotic potential and challenges in urban settings. A 3-month-old female Himalayan kitten was presented to Armonia Pet Care, Makassar, Indonesia, with clinical signs of mange, including alopecia, erythema, hyperkeratosis, and severe pruritus. Diagnosis was confirmed through superficial skin scraping and microscopic identification of N. cati. Treatment involved combined topical antiparasitic therapy (selamectin and sarolaner) with nutritional support, resulting in significant clinical improvement within one week. This case highlights the importance of early diagnosis, appropriate therapy, and environmental management to prevent reinfestation, particularly in urban areas with high risks of cross-contamination.  These findings contribute to the scientific understanding of feline scabies and its clinical management in Indonesian veterinary practice. We recommend routine ectoparasite screening for cats in high-density urban areas, owner education about zoonotic risks, and further studies on the efficacy of combined selamectin-sarolaner therapy in multi-cat households.